2004
DOI: 10.1093/jat/28.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acid-Labile Conjugates of Ketamine and Its Metabolites in Urine Samples Collected from Pub Participants

Abstract: The rapid increase of ketamine (K) abuse worldwide has created a need for a sensitive and reliable detection procedure. Ketamine and its major metabolite, norketamine (NK), are usually determined with gas chromatography-mass spectrometry (GC-MS). Phase II metabolism of K has not been fully investigated. In this report, we studied the phase II biotransformation of ketamine. Urine samples were hydrolyzed with concentrated HCl and alkalinized and extracted with organic solvent. GC-MS (electron impact mode) was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…When the ratios of DHNK to internal standard were compared to the ratio of NK, the excretion amount of DHNK was more than 8-38 times (average 15.6 times) of NK in KT abuser urines (data not shown). Lin and Lua [7] also reported that the DHNK concentration was greatest in 20 of the 24 KT positive urine samples. The concentration of DHNK will be studied with authentic DHNK material in the future.…”
Section: Concentrations Of Kt and Nk In Drug Abuser's Urinesmentioning
confidence: 91%
“…When the ratios of DHNK to internal standard were compared to the ratio of NK, the excretion amount of DHNK was more than 8-38 times (average 15.6 times) of NK in KT abuser urines (data not shown). Lin and Lua [7] also reported that the DHNK concentration was greatest in 20 of the 24 KT positive urine samples. The concentration of DHNK will be studied with authentic DHNK material in the future.…”
Section: Concentrations Of Kt and Nk In Drug Abuser's Urinesmentioning
confidence: 91%
“…Recently, sensitive GC-MS and LC-MS/MS methods have been developed [13][14][15][16][17]19,20,25]. To the best of our knowledge this is the first validated UPLC-MS/MS method for the detection and quantitation of ketamine and norketamine in urine as well as the most sensitive analytical method for both of these analytes to date.…”
Section: Uplc-ms/ms Methods Validation For Ketamine and Norketaminementioning
confidence: 99%
“…This has led to several groups reporting the use [9,10] and need [11,12] for highly sensitive assays that can provide sufficient retrospective detection for ketamine together with other classes of fast acting sedative drugs. Many procedures have been described for detecting ketamine and its active metabolite norketamine in human urine, with varying limits of detection, ranging from 0.5 ng/mL to 25 ng/mL for both compounds [13][14][15][16][17][18][19] but only one group describe a method with an LOD of 0.05 ng/mL for norketamine, which was used to assay samples following intravenous infusion of ketamine for therapeutic purposes [13]. Despite these investigations on the analysis of ketamine, there is a paucity of data regarding the urinary elimination of ketamine and norketamine following oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows the total ion chromatogram derived from drugfree urine spiked with 30 ng/mL of each analyte. Earlier GC-MS studies [9,16,18] reported the quantitation of K and DHNK without derivatization but failed to mention if these two analytes were well resolved. We noted a 60% cross-contribution of m/z 138 ion from K to DHNK when the same concentration of DHNK and K co-elute.…”
Section: Ion Selection For Sim Modementioning
confidence: 99%
“…More specific methods using mass spectrometer as the detector, i.e. gas chromatography-mass spectrometry (GC-MS) [6,7,[9][10][11][12][13][14][15][16][17][18] and liquid chromatography-mass spectrometry (LC-MS) methods [18,19], have been reported. More recently, highly specific approaches based on liquid chromatography-tandem mass spectrometry (LC-MS-MS) [20] and headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS) [21] have also been advocated as effective "screening" methods.…”
Section: Introductionmentioning
confidence: 99%